2019
DOI: 10.2147/opth.s220877
|View full text |Cite
|
Sign up to set email alerts
|

<p>Structure–Function Correlation Using OCT Angiography And Microperimetry In Diabetic Retinopathy</p>

Abstract: PurposeTo evaluate macular vasculature in diabetic retinopathy (DR) with optical coherence tomography angiography (OCTA) and to correlate vessel density (VD) with retinal sensitivity (RS) as a way to assess structural and functional findings in DR.DesignProspective observational cross-sectional study.MethodsDiabetic patients with DR but no clinically significant diabetic macular edema (DME) and healthy subjects were included in this study. All of them underwent comprehensive ophthalmic examination, best correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
(45 reference statements)
1
12
1
Order By: Relevance
“…Therefore, we categorized all RS locations into four groups, based on FD and leakage. At points where leakage was low, RS decreased when FD decreased (group A vs. group B; P < 0.0001, P < 0.007 and P < 0.004 in TCP, SCP and DCP, respectively), as previously reported 9 , 16 . However, contrary to expectations, at points with high leakage, FD only significantly affected RS in the DCP (group C vs. group D; P < 0.0004).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, we categorized all RS locations into four groups, based on FD and leakage. At points where leakage was low, RS decreased when FD decreased (group A vs. group B; P < 0.0001, P < 0.007 and P < 0.004 in TCP, SCP and DCP, respectively), as previously reported 9 , 16 . However, contrary to expectations, at points with high leakage, FD only significantly affected RS in the DCP (group C vs. group D; P < 0.0004).…”
Section: Discussionsupporting
confidence: 79%
“…Fluorescein angiography (FA) studies have demonstrated significant reduction in RS in non-perfused areas 5 , 6 , suggesting that perfusion status affects RS. Unlike FA, optical coherence tomography angiography (OCTA) allows quantification of flow density (FD) 7 : several studies have shown that FD is associated with RS in DR 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…scale and in perifoveal regions. [38][39][40][41] This finding was true for all three retinal vasculature slabs tested. We believe, however, that this is the first article to demonstrate a quantitative, pointwise structure-function relationship between retinal sensitivity and vessel density in DR.…”
Section: Correlating Microperimetry and Octa In Dr Levine Et Almentioning
confidence: 75%
“…The University Hospital of La Candelaria Department of Ophthalmology in Tenerife (Spain) performed a study related to structure-function correlation using optical coherence tomography (OCT) angiography and microperimetry in diabetic retinopathy using the MP-3 system (Nidek, Aichi, Japan) in the year 2019 [2].…”
Section: Dear Editormentioning
confidence: 99%